1999
DOI: 10.1095/biolreprod60.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transfer in the Rhesus Monkey: Practical and Basic Implications1

Abstract: In early 1997, the birth of a lamb after transfer of the nucleus from an adult mammary gland cell into an enucleated oocyte, along with the production of rhesus monkeys by nuclear transfer of embryonic cells, marked a reemergence of the field of mammalian cloning. Clonally derived rhesus monkeys would be invaluable in biomedical research, and the commercial interests in transgenic sheep and cattle propagated by cloning are substantial. Nuclear transfer technology is under consideration in human in vitro fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…identical offspring. Blastomere nuclear transSplits have been frozen and transferred sucfer has been successful [3.8% live fetuses per cessfully; clones with differing birth dates embryos transferred (8)]. Splitting results in have numerous applications: e.g., pheno-31% pregnancies and 8% births, and similar typic analysis of an offspring before propresults were obtained by using four-to eight-agating clones; serial transfer of stem cells cell blastomere nuclear transfer in rhesus, i.e., to address cellular aging beyond life ex-24% (4117) pregnancies and 12% (2117) pectancy; and investigating simultaneous births (8).…”
mentioning
confidence: 99%
“…identical offspring. Blastomere nuclear transSplits have been frozen and transferred sucfer has been successful [3.8% live fetuses per cessfully; clones with differing birth dates embryos transferred (8)]. Splitting results in have numerous applications: e.g., pheno-31% pregnancies and 8% births, and similar typic analysis of an offspring before propresults were obtained by using four-to eight-agating clones; serial transfer of stem cells cell blastomere nuclear transfer in rhesus, i.e., to address cellular aging beyond life ex-24% (4117) pregnancies and 12% (2117) pectancy; and investigating simultaneous births (8).…”
mentioning
confidence: 99%
“…The long-acting agonist could be administered at any point during the third week of the menstrual cycle, as opposed to Days 21,22, or 23 with the short-acting form. Once menses had occurred, stimulations for this group could be initiated at any point during the month following the single injection.…”
Section: Discussionmentioning
confidence: 99%
“…Short-acting antagonist down regulation in rhesus monkeys has been reported by Zelinski-Wooten et al [21], with 51% mature oocyte production, as well as by SanchezPartida et al [23], with a 57% maturity rate. In addition, Wolf et al [22] reported an average yield of 16.7 oocytes per retrieval, and Hewitson et al [33] reported an average oocyte yield of 27 oocytes per retrieval and 53.7% maturity using short-acting antagonist down regulation. Cseh et al [28] induced down regulation in baboons with a long-acting agonist similar to Lupron Depot (goserelin acetate) followed by a stimulation protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear transfer was also tried in the rhesus monkey [63,113]. We therefore have begun studies on oocyte activation, pronucleus formation, pronucleus fusion and subsequent embryo development.…”
Section: Intracytoplasmic Sperm Injection (Icsi)mentioning
confidence: 99%